Checklist of free-living marine nematodes from intertidal sites along the central west coast of India - Punyasloke Bhadury; Nityananda Mondal; Kapuli Ansari; Priscilla Philip; Reshma Pitale; Amruta Prasade; Pooja Nagale; Deepak Apte (Check List, 2015)
The present study provides a checklist of free-living marine nematode species from nine intertidal sites located along the central west coast of India covering an area between latitudes 16°33′08.47″ N and 16°38′50.75″ N and longitudes 073°19′30.13″ E and 073°23′34.97″ E. The list includes 33 species of marine nematodes belonging to 20 genera and 13 families. The occurrence of nematode species identified appears to be correlated to character of the sediments across sampled intertidal sites. Ten families were encountered in sandy sites while in muddy sites the number was ten. Three families, namely Camacolaimidae, Ironidae, and Microlaimidae, were exclusive to the sandy sites, while Anoplostomatidae, Comesomatidae, and Linhomoeidae were only found across muddy sites. Some of the dominant free-living marine nematode groups encountered across all sites was represented by the genera Ptycholaimellus, Viscosia, Oncholaimus, Halalaimus, and species such as Sphaerolaimus balticus and Metachromadora suecica.